2014
DOI: 10.1161/circimaging.113.000989
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Strain Analysis by 2-Dimensional Speckle Tracking Echocardiography Improves Diagnostics of Coronary Artery Stenosis in Stable Angina Pectoris

Abstract: Exercise testing is recommended as a first-line diagnostic test in patients with suspected SAP, 9 although the limited sensitivity and specificity have been criticized. 10 Thus, it would be encouraging if 2DSE performed at rest could improve the diagnostic accuracy of the exercise test because both an Background-Two-dimensional strain echocardiography detects early signs of left ventricular dysfunction; however, it is unknown whether myocardial strain analysis at rest in patients with suspected stable angina p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
119
3
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 24 publications
20
119
3
7
Order By: Relevance
“…The present study found that GLS had highly significant positive correlation with EF (r = 0.37, p = 0.001). This result in concordant with results of, Biering-Soerensen et al [17], Evensen et al [18] and Delgado et al [30].…”
Section: Correlation Between Gls and Efsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study found that GLS had highly significant positive correlation with EF (r = 0.37, p = 0.001). This result in concordant with results of, Biering-Soerensen et al [17], Evensen et al [18] and Delgado et al [30].…”
Section: Correlation Between Gls and Efsupporting
confidence: 93%
“…We found that GLS declined incrementally with increasing severity of CAD defined by increasing number of stenotic coronary vessels. This finding was similar to results of Biering-Soerensen et al [17] and also the studies reported by Gaibazzi et al [20] and Choi et al [22] which showed similar GLS values through different CAD categories. Patients with normal coronaries had a mean GLS of -22 ±1.5%, single or double vessel disease -19.4 ± 2.4 %, and triple-vessel or left main disease -18 ± 2.3%.…”
Section: Association Between Gls and Severity Of Cadsupporting
confidence: 92%
See 2 more Smart Citations
“…SAP was defined as chest pain or discomfort (angina) suspected to be caused by myocardial ischemia 21, 22. Anginal symptoms were considered stable if they had been occurring for several weeks without deterioration and were typically induced by activity or stress 22.…”
Section: Methodsmentioning
confidence: 99%